2011
DOI: 10.1002/humu.21644
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the nonallelic homologous recombination hotspot PRS3 associated with type-3NF1deletions

Abstract: Nonallelic homologous recombination (NAHR) is the major mechanism underlying recurrent genomic rearrangements, including the large deletions at 17q11.2 that cause neurofibromatosis type 1 (NF1). Here, we identify a novel NAHR hotspot, responsible for type-3 NF1 deletions that span 1.0 Mb. Breakpoint clustering within this 1-kb hotspot, termed PRS3, was noted in 10 of 11 known type-3 NF1 deletions. PRS3 is located within the LRRC37B pseudogene of the NF1-REPb and NF1-REPc low-copy repeats. In contrast to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 68 publications
(97 reference statements)
0
23
0
2
Order By: Relevance
“…Type 1 deletions are ∼1.5 Mb in size with breakpoints between the low copy repeat (LCR) domains NF1‐REPa and NF1‐REPc [Lopez Correa et al., ]. Type 2 deletions are 1.2 Mb long and with breakpoints in JJAZ1 and its pseudogene [Kehrer‐Sawatzki et al., ], and type 3 deletions are 1.0 Mb long with breakpoints between the LCR domains NF1‐REPb and NF1‐REPc [Zickler et al., ]. Our analysis of seven lymphocyte DNA samples from individuals with NF2 showed that the deletion sizes were different in every case, with one recurrent 5′ breakpoint identified in two samples.…”
Section: Discussionmentioning
confidence: 89%
“…Type 1 deletions are ∼1.5 Mb in size with breakpoints between the low copy repeat (LCR) domains NF1‐REPa and NF1‐REPc [Lopez Correa et al., ]. Type 2 deletions are 1.2 Mb long and with breakpoints in JJAZ1 and its pseudogene [Kehrer‐Sawatzki et al., ], and type 3 deletions are 1.0 Mb long with breakpoints between the LCR domains NF1‐REPb and NF1‐REPc [Zickler et al., ]. Our analysis of seven lymphocyte DNA samples from individuals with NF2 showed that the deletion sizes were different in every case, with one recurrent 5′ breakpoint identified in two samples.…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that the interaction between microtubules and the actin cytoskeleton in association with membrane-associated proteins regulates cell shape and cellular remodelling (reviewed by Basu and Chang 2007; Bezanilla et al 2015). Since ADAP2 interacts with the microtubule/actin cytoskeleton, it may function as a cytoskeleton cross-talker that increases microtubule stability and modulates actin reorganisation and hence cellular morphology (Zucotti et al 2012). Disturbances of the cytoskeletal organisation in myocytes during embryonal development may be responsible for the cardiovascular malformations observed in patients with NF1 microdeletions.…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 99%
“…1) (Bengesser et al 2010; Pasmant et al 2010; Zickler et al 2012). As their name suggests, atypical large NF1 deletions do not exhibit recurrent breakpoints and are quite heterogeneous in terms of their size and the number of genes located within the deleted region (Upadhyaya et al 1996; Cnossen et al 1997; Dorschner et al 2000; Kehrer-Sawatzki et al 2003, 2005, 2008; Venturin et al 2004a; Gervasini et al 2005; Mantripragada et al 2006; Pasmant et al 2008, 2009, 2010; Vogt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Protein encoded by LRRC37B gene is not well-characterized yet. However, a recent study has reported that the LRRC37B locus may harbour non-allelic homologous recombination hotspot, a major mechanism involved in chromosomal rearrangements [41]. SH3GL1P1 is a pseudogene with no known function.…”
Section: Discussionmentioning
confidence: 99%